EMC2: an emergency management system using mobile cloud computing. Issue 2 (1st March 2020) - Ramasamy, V.; Gomathy, B.; Sarkar, Joy Lal; Panigrahi, Chhabi Rani; Pati, Bibudhendu; Majumder, Abhishek
Abstract : A natural or unexpected man‐made emergency may occur at any time and which affects the economy as well as human life of the country. The most important task in an emergency is to collect the essential information about the emergency places and do a proper analysis to take effective action. In those situations, mobile gadgets are very much helpful to collect the information in a significant way. The mobile devices have certain limitations such as less battery power, lack of Internet connectivity for data transmission or less computational resources. So the energy hungry applications can be offloaded to the cloud to reduce the workload of the mobile devices. To overcome these problems, the authors propose an emergency management system named as EM C 2, which follows peer‐to‐peer communication using Bluetooth technology. EM C 2 first detects the available mobile devices present in a network using mobile probing service (MPS) and then it chooses the suitable mobile device among them using mobile ranking service (MRS). EM C 2 also determines the best network resources while roaming in heterogeneous access networks (HANs). The experimental results of authors– proposed EM C 2 approach shows the increased performance and out‐performs in terms of receiving time as compared to the baseline algorithm.